2020
DOI: 10.1038/s41699-020-00179-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-driven WSe2 photodetectors enabled with asymmetrical van der Waals contact interfaces

Abstract: Self-driven photodetectors that can detect light without any external voltage bias are important for low-power applications, including future internet of things, wearable electronics, and flexible electronics. While two-dimensional (2D) materials exhibit good optoelectronic properties, the extraordinary properties have not been fully exploited to realize high-performance self-driven photodetectors. In this paper, a metal–semiconductor–metal (MSM) photodetector with graphene and Au as the two contacts have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 53 publications
0
74
0
Order By: Relevance
“…We found that thinner Pt layers and Au layers thicker than approximately 40 nm were optimal, and our PV devices were designed following these considerations to improve their efficiency. Finally, we analyzed the electrical properties of the bottom contact using lateral WSe 2 FETs where the WSe 2 flake was transferred onto the prepatterned pair of symmetric Au or Pt contacts (Figure S14), thus forming vdW Pt/WSe 2 and Au/WSe 2 contacts. , Figure e shows approximately a three orders of magnitude difference between current levels in the transfer characteristics of Au- and Pt-contacted FETs when the gate voltage is swept from 20 V to −20 V. This difference arises from the difference in the effective barrier heights (314 meV for the Au/WSe 2 contact and 162 meV for the Pt/WSe 2 contact), which were obtained from the Arrhenius plots shown in Figure f. These results show that the material choice for bottom vdW contacts in such vertical PV devices is even more critical for PV performance than in the case of electrodes conventionally deposited on material surfaces (for example, by electron beam evaporation systems), where the difference in the WFs between Au and Pt can be negated by the Fermi-level pinning.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We found that thinner Pt layers and Au layers thicker than approximately 40 nm were optimal, and our PV devices were designed following these considerations to improve their efficiency. Finally, we analyzed the electrical properties of the bottom contact using lateral WSe 2 FETs where the WSe 2 flake was transferred onto the prepatterned pair of symmetric Au or Pt contacts (Figure S14), thus forming vdW Pt/WSe 2 and Au/WSe 2 contacts. , Figure e shows approximately a three orders of magnitude difference between current levels in the transfer characteristics of Au- and Pt-contacted FETs when the gate voltage is swept from 20 V to −20 V. This difference arises from the difference in the effective barrier heights (314 meV for the Au/WSe 2 contact and 162 meV for the Pt/WSe 2 contact), which were obtained from the Arrhenius plots shown in Figure f. These results show that the material choice for bottom vdW contacts in such vertical PV devices is even more critical for PV performance than in the case of electrodes conventionally deposited on material surfaces (for example, by electron beam evaporation systems), where the difference in the WFs between Au and Pt can be negated by the Fermi-level pinning.…”
Section: Results and Discussionmentioning
confidence: 99%
“…6 shows the R values of our InSe photodetectors, in comparison with those of other 2D-material-based self-powered photodetectors, at various wavelengths. 14,16,29,32,33,45–57 A p–n junction, doping, and asymmetric contacts were introduced to create built-in potentials in previously reported self-powered photodetectors. Accompanied by such an approach to induce a built-in potential, our vertical heterostructure with transparent FLG/In top contact and bottom Au contact underneath the InSe develops a distinctively large built-in field with a short transit time.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported an asymmetrical metal–semiconductor–metal (MSM) photodetector by using graphene and Au as the electrode contacting the WSe 2 flake. The graphene and WSe 2 were vertically stacked in part to form the van der Waals contact via the dry-transfer method [ 65 ]. Figure 4 a is an illustration of a graphene-WSe 2 -Au photodetector on a SiO 2 /Si wafer substrate.…”
Section: Self-powered Sensorsmentioning
confidence: 99%
“…( f ) Dependence of the open-circuit voltage (Voc) on gate voltage bias and light power density at 780 nm illumination. Reproduced with permission from [ 65 ]. Copyright 2020, Springer Nature.…”
Section: Figurementioning
confidence: 99%